Penggunaan Media Roda Pintar Untuk Meningkatkan Kemampuan Menulis Anak Usia 4-5 Tahun Di Sukawargi - Jubaedah, Endah; Asiah, Euis; Maosul, Asep (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by observational data that shows the low achievement of writing skills in early childhood at Al Waladul Huda Kindergarten with the discovery of several problems including; writing skills in group A are still lacking, children have not been able to make a meaningful scribble, children have not been able to write letters from A-Z. The purpose of this study is to describe the use of Smart Wheel media to improve writing skills in children aged 4-5 years. The subjects in this study were 10 respondents with 6 male subjects and 4 female subjects. The type of research used in this study is qualitative research with a classroom action research design or PTK. The results of this study indicate that the use of Smart Wheel media to improve writing skills in children aged 4-5 years shows a significant increase, can be seen from the percentage of success, from the results of initial observations there are 0% of children developing very well, 0% of children developing according to expectations, 40% of children starting to develop and 60% of children have not developed. After implementing the use of Smart Wheel media to improve writing skills in children aged 4-5 years, the final results of cycle I reached a 60% increase in writing skills in children aged 4-5 years, and the final results of cycle II reached 100%. Keywords: Early Childhood, Smart Wheel Media, Writing